2016
DOI: 10.1111/are.13154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fish meal replacement by Chlorella meal with dietary cellulase addition on growth performance, digestive enzymatic activities, histology and myogenic genes’ expression for crucian carp Carassius auratus

Abstract: This study was conducted to investigate the effects of fish meal (FM) replacement by Chlorella meal (CM) with dietary cellulase supplementation on growth performance, digestive enzymatic activities, histology and myogenic genes' expression in crucian carp Carassius auratus (initial body weight: 2.90 AE 0.02 g, mean AE SEM). Six isonitrogenous diets were formulated at two cellulase levels (0 and 2 g kg À1 ). At each cellulase level, CM was added at three levels of 0, 533.1 and 710.8 g kg À1 to substitute 0, 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 46 publications
4
41
0
Order By: Relevance
“…In the present study, FCR decreased and PER increased with increasing dietary RCM levels, which suggested that high levels of RCM in diets could be more effectively used by crucian carp. Dietary RCM replacement decreased HSI, in agreement with our previous study about fishmeal replacement by Chlorella meal (Shi, Luo, Chen, Wei, et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, FCR decreased and PER increased with increasing dietary RCM levels, which suggested that high levels of RCM in diets could be more effectively used by crucian carp. Dietary RCM replacement decreased HSI, in agreement with our previous study about fishmeal replacement by Chlorella meal (Shi, Luo, Chen, Wei, et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Another study showed the replacement of fish meal by Chlorella meal supplemented by dietary cellulase to crucian cap Carassius auratus and after evaluated the growth performance, digestive enzymatic activities, histology and myogenic genes' expression they conclude that Chlorella meal could totally replace the fish meal [115].…”
Section: Microalgae In Fish Feedmentioning
confidence: 99%
“…Shi et al. () showed that the substitution of dietary fish meal with Chlorella meal significantly increased amylase activity of crucian carp, C. auratus . Furthermore, Radhakrishnan et al.…”
Section: Discussionmentioning
confidence: 99%